Photogrammetry - Cameron Stebbing (Architecture Image Studies Scientific Journal)
This paper explores the ontology of photogrammetry beyond its role as an analytical process to accurately record places. It identifies photogrammetric scans as hybrid artefacts, which can capture a wide array of spatial and temporal information upon their surfaces. Such traces are explored through the work of Object Oriented Ontology philosopher Timothy Morton, with cues also taken from the work of John Ruskin who places emphasis on the stained surface as the site of a building’s value. Presented alongside these propositions are a series of photogrammetric studies where antagonistic and disruptive data is maintained in the outcome to allow the manifestation of these concealed relationships. The awareness of these syncopated chronologies questions the futurity of a recorded object, accommodating both its presence and absence. What is argued here can allow the scan to become a site for speculation and proposition beyond the deferral to a real-world object.